2018
DOI: 10.33881/1657-2513.art.18201
|View full text |Cite
|
Sign up to set email alerts
|

Association between occupational voice use and occurrence of voice disorders: a meta-analysis

Abstract: Purpose: This meta-analysis has two aims: 1) to provide a quantitative assessment of the occurrence of voice disorders among different occupational voice users, 2) and to determine whether being an occupational voice user (teacher, broadcaster, call-center worker, etc.) is associated with an increased occurrence of voice disorders. Method: A random-effect meta-analysis of the available scientific literature was conducted on the occurrence of voice disorders among occupational voice users. Comprehensive literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In contrast, Cutiva et al reported that the prevalence of voice disorders among occupational voice users was less than 11 per cent when shorter recall period studies were included. 3 The assessment method demonstrated a significant contribution to the prevalence rates: studies based on clinical examinations such as stroboscopy and video laryngoscopy showed higher prevalence rates of voice disorders compared with studies using questionnaires to assess voice disorders. We found that the subjective voice analysis using maximum phonation time and Voice Handicap Index-10 showed significant differences pre-and post-shift among teleoperators (maximum phonation time ( p < 0.018) and Voice Handicap Index ( p < 0.011)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Cutiva et al reported that the prevalence of voice disorders among occupational voice users was less than 11 per cent when shorter recall period studies were included. 3 The assessment method demonstrated a significant contribution to the prevalence rates: studies based on clinical examinations such as stroboscopy and video laryngoscopy showed higher prevalence rates of voice disorders compared with studies using questionnaires to assess voice disorders. We found that the subjective voice analysis using maximum phonation time and Voice Handicap Index-10 showed significant differences pre-and post-shift among teleoperators (maximum phonation time ( p < 0.018) and Voice Handicap Index ( p < 0.011)).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published by Cutiva et al found a total of 18 cross-sectional studies. 3 The authors demonstrated that most of the included studies carried out voice assessments based on questionnaires and found that the prevalence of voice disorders among occupational voice users ranged from 11 to 18 per cent. Moreover, occupational voice users showed up to four times more likelihood of having a voice disorder than nonoccupational voice users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It is not uncommon for professional voice users to require some degree of treatment, whether that includes voice therapy and/or medical intervention, but the patient's priority is often a quick recovery and returns to work. Source: Adapted from Cantor-Cutiva (2018) 22 per week, the environment in which they use the voice, and access to amplification or the need to project the voice. It may also be necessary to discuss voice use outside of their occupation to understand whether their home or social life might be contributing to any voice difficulty.…”
Section: Laryngeal Anatomy and Physiologymentioning
confidence: 99%